2007
DOI: 10.1111/j.1477-8947.2007.00130.x
|View full text |Cite
|
Sign up to set email alerts
|

Transfrontier conservation areas: Integrating biodiversity and poverty alleviation in Southern Africa

Abstract: Sub-Saharan Africa continues to face the daunting challenge of alleviating poverty due to slow economic growth. In southern Africa, most countries are adopting policies that promote the integration of biodiversity conservation and rural development to contribute to rural poverty alleviation. Numerous approaches have been undertaken in this endeavour, including Transfrontier Parks (TFPs) and Transfrontier Conservation Areas (TFCAs). This paper discusses some of the limitations of the TFPs. In conclusion I posit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
49
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 64 publications
(51 citation statements)
references
References 10 publications
2
49
0
Order By: Relevance
“…Community-based conservation is regarded as a practical approach to stemming biodiversity loss in developing countries (Mehta & Kellert, 1998;Munthali, 2007). The community based natural resource management (CBNRM) program in Namibia is one such example, where the sustainable use and conservation of biodiversity aims to allow local communities to derive direct benefits from their wildlife management efforts (Paterson et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Community-based conservation is regarded as a practical approach to stemming biodiversity loss in developing countries (Mehta & Kellert, 1998;Munthali, 2007). The community based natural resource management (CBNRM) program in Namibia is one such example, where the sustainable use and conservation of biodiversity aims to allow local communities to derive direct benefits from their wildlife management efforts (Paterson et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…To make matters worse, the United States Agency for International Development (USAID) and a Peace Parks Foundation consultant concluded that the area along the banks of Shingwedzi River where the majority of Mozambican people live is the most suitable for sustaining viable wildlife and tourism development Milgroom, Spierenburg, 2008). Resident people are being forced to relocate in order to create extra space for wildlife and to make the park more attractive for private investment (Ferreira, 2006;Munthali, 2007;Spierenburg et al, 2008;Milgroom, Spierenburg, 2008;Lunstrum, 2010). As a result of these controversies, Wolmer (2003: 266) considers TFCAs as the latest in a line of top-down, market-oriented environmental interventions pushed on Africa by international bureaucracies (including the World Bank, bilateral donors, international conservation organizations) and the private sector.…”
Section: Synopsis Of Transfrontier Conservation Areas In Southern Africamentioning
confidence: 99%
“…In other words, state borders no longer make a difference in the borderless world. Essentially, conservation beyond the borders of protected areas that transcends multiple land owners including communal, state and private land encourages multiple land use practices (Ferreira, 2006;Munthali, 2007). The goal of multiple-land use practices is to improve rural livelihoods whilst promoting biodiversity conservation ( Van der Linde et al, 2001;Munthali, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…Transboundary protected area management (TBPAM) is an influential extension of PA governance in Africa (Muhweezi et al 2007, Munthali 2007. It is defined as joint governance of adjacent PAs across boundaries between sovereign countries, seeing the "humanly constructed borders" as disruptive for ecological systems (Van Amerom 2002).…”
Section: Introductionmentioning
confidence: 99%